0
$\begingroup$

I'm a little bit confused about how the limits of integration are changed if we change the variable of integration. I'm not sure what exactly I don't understand, so I below I will write some false statements that seem true to me, and I ask to point out what exactly is wrong (and why).

For instance, $\int_0^1dx=1$, so $\int_0^1d(-y)=-\int_0^1dy=-1$. But $-y$ can be treated as a variable $\xi, $ so $\int_0^1d(-y)=\int_0^1d\xi=1$ by the first equality. What am I doing wrong?

Next, if $0\le t \le 1$, then $-1\le -t \le 0$. Thus shouldn't be true that $\int_0^1dt=\int_{-1}^0d(-t) $?

Does all of this have to do with "The Substitution Rule for Definite Integrals"? I wasn't able to relate it to these cases, since I don't see any derivatives which are used in that theorem.

$\endgroup$
0
$\begingroup$

$$ \int\limits_0^1 dx \neq \int\limits_0^1 d(-y) $$

If you make a proper change of variables, you might say something like $x = -y$, in which case $dx = -dy$, further $x = 0$ to $x = 1$ becomes $y = 0$ to $y = -1$:

\begin{align} \int\limits_{x\ =\ 0}^{x\ =\ 1} dx = -\int\limits_{y\ =\ 0}^{y\ =\ -1}dy = -(-1 - 0) = +1 && \text{q.e.d.} \end{align}

Here's a slightly more complicated example:

$$ \int\limits_0^8 xdx = \frac{1}{2}\left(8^2 - 0^2\right) = 32 $$

Let's try $x = -y^3$. We find that $dx = -3y^2dy$ and that from $x = 0$ to $x = 8$ means $y = 0$ to $y = -2$:

\begin{align} \int\limits_0^8 xdx =&\ \int\limits_0^{-2}\left(\left(-y^3\right)\left(-3y^2\right)\right)dy \\ =&\ 3\int\limits_0^{-2}y^5dy = \frac{3}{6}\left((-2)^6 - 0^6\right) \\ =&\ \frac{1}{2}\cdot2^6 = 2^5 = 32 && \text{q.e.d} \end{align}

$\endgroup$
0
$\begingroup$

Suppose that you have the integral defined by $\int_a^b f(x)\,\mathrm dx$ and you make the change of variable $x=g(y)$ for some differentiable and injective $g$ in $[a,b]$, then you have that $\mathrm dx=g'(y)\,\mathrm dy$ and that if $x=a$ then $y=g^{-1}(a)$. Same for the $b$, that is, if $x=b$ then $y=g^{-1}(b)$, because $g$ is invertible in $[a,b]$.

Thus

$$\int_a^b f(x)\,\mathrm dx=\int_{g^{-1}(a)}^{g^{-1}(b)}(f\circ g)(y)\,g'(y)\,\mathrm dy$$

In your example you have the change of variable $x=-y$ thus $0=-y$ and $1=-y$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.